Diseño de un sistema de gestión en control y seguridad industrial para una empresa de servicios de limpieza - Batallas Cueva, Silvana (2009)
As part of their overall development, the companies should consider in their management the control and industrial safety aspects, which help to maintain the welfare of workers and all the persons that are related to the company. This article shows the results of the work in a company that offers cleaning services, starting with the diagnosis of the current situation of it, and then the design of the control and industrial security system management force throughout the organization, based on the risk prevention, hazard identification and risk assessment. To facilitate the process of implementing the system, it provides methodologies and techniques, and also a software to support the system.